Australian Soils and Landscapes : An Illustrated Compendium - McKenzie, Neil, Jacquier, David; Isbell, Ray; Brown, Katharine (Collingwood CSIRO Publishing, 2004)
A unique compendium of the most important and widespread soils of Australia and their associated landscapes.
Include Tables, Illustrations, Endnotes, References and Index.
An Illustrated Compendium.
Keywords: Soils -- Australia -- Landscapes